How Starting Strategy and Network Structure Shape Problemistic Search: An Examination of Venture Capital Firms. (September 2022) - Duke, Jake; Havakhor, Taha; Mui, Rachel; Parker, Owen
Building on the behavioral theory of the firm, we empirically examine how starting strategies and syndication networks can influence venture capital (VC) firms' problemistic search. We propose that: (a) depending on a VC's strategic starting point, that is, the VC's extent of specialization, the directionality of problemistic search may change to either expanding or contracting search activities; and (b) depending on search direction, structural holes in syndication networks can either impede or facilitate the problemistic search process. In a sample of U.S. VC firms, we find results consistent with our predictions, which have important implications for entrepreneurship and organizational strategy research.